Analisis Yuridis terhadap Notaris yang Berkewajiban Amanah Menurut Pasal 16 Udang-Undang no. 2 Tahun 2014 tentang Jabatan Notaris - Nugraha, Naufal Aji; Silviana, Ana (Legal Standing : Jurnal Ilmu Hukum, 2025)
A notary is a public official appointed by the state to carry out part of the public authority, especially in making authentic deeds that have legal force. The role of a notary must comply with various legal provisions stipulated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary (Notary Position Law). One of the main obligations that must be carried out by a notary is to act in a trustworthy manner, as stipulated in Article 16 Paragraph (1) Letter a of the Notary Position Law. In Islam, the principle of trustworthiness has a position as one of the basic values that must be applied in community and state life. Trustworthiness is a commendable trait recommended by the Qur'an and Hadith. The obligation of a notary to act in a trustworthy manner as stipulated in the Notary Position Law has strong relevance to the teachings of Islamic law. A study of the obligation of a notary to act in a trustworthy manner according to Article 16 Paragraph (1) Letter a of the Notary Position Law, when viewed from the perspective of Islamic law, is important to provide a more comprehensive understanding of the relationship between positive law and Islamic values. This study aims to analyze the obligation of notaries to act in a trustworthy manner, identify its relevance to the principle of trustworthiness in Islamic law, and examine the law of violations of this obligation.